Effect of body condition at lambing on the postpartum anestrum of Merino Beira Baixa ewe - Rodrigues, J.P. Várzea (2000)
The main goal of this study was to identify the percentage of ewes with resumption of postpartum ovarian activity (POA) and the postpartum anestrum lenght (PAL) in function of body condition score (BC) at lambing.